2019
DOI: 10.1016/j.celrep.2019.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Inputs from Sequentially Developed Parallel Fibers Are Required for Cerebellar Organization

Abstract: Highlights d Establishing selective blockade of PF bundles in the developing cerebellum d Unbiased inputs from PFs are important for cerebellar network development d The level of importance is different according to the time and location of PF inputs d The unbiased PF inputs during development affect motor coordination in adults

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 75 publications
1
18
0
Order By: Relevance
“…Of note, agenesis of the cerebellar vermis has been described in individuals with CHD8 (p.Cys1691Tyr) mutations (Firth et al, 2009; DECI-PHER 259269), suggesting that CHD8 deficiency results in abnormal development of the cerebellum not only in mice but also in humans. Given that synaptic transmission from PFs of CGNs to Purkinje cells has been shown to be highly related to motor function (Kashiwabuchi et al, 1995;Hirai et al, 2005;Kakegawa et al, 2009;Park et al, 2019), it is possible that the motor dysfunction apparent in Atoh1-Cre/Chd8 L F/F mice is attributable to disruption of cerebellar circuits caused by the reduced number and altered synaptic function of CGNs. Our ChIP-seq data for CHD8 in GNPs showed that CHD8 was bound to the promoter regions of many synapse-related genes, including Slc17a7, and thereby directly regulates the expression of these target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, agenesis of the cerebellar vermis has been described in individuals with CHD8 (p.Cys1691Tyr) mutations (Firth et al, 2009; DECI-PHER 259269), suggesting that CHD8 deficiency results in abnormal development of the cerebellum not only in mice but also in humans. Given that synaptic transmission from PFs of CGNs to Purkinje cells has been shown to be highly related to motor function (Kashiwabuchi et al, 1995;Hirai et al, 2005;Kakegawa et al, 2009;Park et al, 2019), it is possible that the motor dysfunction apparent in Atoh1-Cre/Chd8 L F/F mice is attributable to disruption of cerebellar circuits caused by the reduced number and altered synaptic function of CGNs. Our ChIP-seq data for CHD8 in GNPs showed that CHD8 was bound to the promoter regions of many synapse-related genes, including Slc17a7, and thereby directly regulates the expression of these target genes.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of motor impairments and electrophysiological changes in Purkinje cells in our agranular mice was surprising, given that silencing granule cell synapses results in minor changes in Purkinje cell firing (Galliano et al, 2013). Furthermore, in multiple models, impairing parallel fiber synapses results in motor impairments that can be assessed with the rotor rod assay (Aiba et al, 1994;Park et al, 2019), which we could not do due to the severity of motor impairment in En1 Cre/+ ;Atoh1 fl/mice. Taking these results together, from a technical standpoint, when one seeks to resolve developmental mechanisms, we must not only consider what is manipulated, but also how it is manipulated.…”
Section: Discussionmentioning
confidence: 80%
“…We also examined the morphology of P14 Purkinje cells since previous studies suggest that decreased excitatory input alters Purkinje cell dendrite outgrowth (Bradley and Berry, 1976;Park et al, 2019). Using Golgi-Cox staining, we found that Purkinje cells in En1 Cre/+ ;Atoh1 fl/mice had stunted and smaller dendritic arbors compared to controls (Figure 2F).…”
Section: Purkinje Cells In En1mentioning
confidence: 96%
“…Mosaic analysis with double markers (MDAM) can reveal the individual morphology of developing CGNs but it requires specific lines and complex genetic crosses ( Zong et al, 2005 ). Viral vectors have been used to express fluorescent proteins in developing CGNs but the delay between the infection and the transgene expression does not allow to observe the early phases of CGN development in the EGL ( Park et al, 2019 ). The size of the transgene is also limited.…”
Section: Discussionmentioning
confidence: 99%